TAKLIK TALAK DALAM HUKUM PERKAWINAN DI INDONESIA DAN IMPLEMENTASINYA DI PENGADILAN AGAMA - Abdul Latif; Lilik Andar Yuni; Abusiri Abusiri (STAI ALHIKMAH Jakarta, 2023)
AbstractThis article is intended to prove the implementation of a violation of the marriage agreement (taklik talak) in the Samarinda Religious Court. As it is known that one of the purposes of marriage is to form a lasting and harmonious family. However, marriage does not always go as expected. Many problems occur in marriage, which causes the purpose of marriage cannot be fulfilled. If so, then divorce becomes a solution for the disharmonious household. One of the causes of divorce is the violation of the marriage agreement (taklik talak). The marriage agreement is one of the institutions regulated in marriage law in Indonesia, especially in the Compilation of Islamic Law (CIL). This marriage agreement is a form of protection of women's rights in the household if at any time the husband acts arbitrarily. From the results of the study, which is a normative legal research, with a legal approach and a case approach, it is proven that the marriage agreement (taklik talak) as one of the reasons for divorce has been well implemented in the Samarinda Religious Court. AbstrakArtikel ini dimaksudkan untuk membuktikan adanya implementasi pelanggaran taklik talak di pengadilan agama Samarinda. Sebagaimana diketahui bahwa salah satu tujuan perkawinan adalah untuk membentuk keluarga yang langgeng dan harmonis. Namun demikian tidak selamanya perkawinan berjalan sesuai dengan yang diharapkan. Banyak problem yang terjadi dalam perkawinan, yang menyebabkan tujuan perkawinan tersebut tidak bisa terpenuhi. Jika sudah demikian, maka perceraian menjadi solusi bagi rumah tangga yang tidak harmonis tersebut. Salah satu penyebab terjadinya perceraian adalah terjadinya pelanggaran taklik talak. Taklik talak adalah salah satu lembaga yang diatur dalam hukum perkawinan di Indonesia, khususnya dalam Kompilasi Hukum Islam (KHI). Taklik talak ini merupakan salah satu bentuk perlindungan hak perempuan dalam rumah tangga jika sewaktu-waktu pihak suami bertindak sewenang-wenang. Dari hasil studi yang merupakan penelitian hukum normatif, dengan pendekatan undang-undang dan pendekatan kasus ini terbukti bahwa taklik talak sebagai salah satu alasan perceraian sudah terimplementasi dengan baik di Pengadilan Agama Samarinda.